The relationship between job satisfaction, burnout syndrome and depressive symptoms: An analysis of professionals in a teaching hospital in Brazil - Oliveira, Alan Maicon de; Silva, Marcus Tolentino; Galvão, Taís Freire; Lopes, Luciane Cruz (Medicine (Baltimore), 2018)
Research shows an instability in the way workers in the healthcare field live, and a prevalence of an unhealthy lifestyle. Exhaustion, an overload of obligations and responsibilities and dissatisfaction are all factors that may result in both physical and mental disorders. The aim of our study is to analyze the association between individual and occupational aspects of hospital workers and their job satisfaction, burnout syndrome, and depressive symptoms, as well as the relationship between these 3 factors.A transversal study was carried out from August to November 2016 in a teaching hospital that is a reference in healthcare to 13 cities in the State of São Paulo, Brazil. Workers with an employment relationship of a period of 3 months or longer were included in the study. Subjects for the study were recruited through random probability sampling. Data were collected using psychometric tools in order to analyze job satisfaction (Job Satisfaction Survey [JSS]), the presence of burnout syndrome (Maslach Burnout Inventory [MBI]) and depressive symptoms (Patient Health Questionnaire-9). Adjusted analyses were conducted and the prevalence ratio (PR) was calculated using Poisson regression. The partial least squares structural equation modeling (PLS-SEM) was used for the analyses.The final sample of this study comprised 271 professionals. Administrative workers or technical support workers from the hospital showed to be more satisfied in their jobs compared to the healthcare professionals (P = .02). Time of professional activity was also associated with job satisfaction (P = .03). Men displayed burnout syndrome approximately twice as often as women (PR = 1.98; 95% CI: 1.03-3.79; P = .04). Workers who had a low household income presented a predominance twice as high of depressive symptoms (PR = 2.84; 95% CI: 1.24-6.51; P = .01). PLS-SEM confirmed the causal and inverse relationship between burnout syndrome and job satisfaction (P < .001). Depressive symptoms were considered predictors for professional exhaustion (P < .001).Personal and occupational factors of hospital workers were associated with job satisfaction, burnout syndrome, and depressive symptoms. The absence of burnout was identified as a predictive aspect for job satisfaction, and depressive symptoms as a predictor for professional exhaustion.